PENERAPAN DATA MINING UNTUK PENGELOLAAN DATA REKAM MEDIS MENGGUNAKAN METODE K-MEANS CLUSTERING PADA RUMAH SAKIT ROYAL PRIMA MEDAN - Winda Nia Purba; Gamaliel Armando Sembiring; Mawar Theresia Turnip; Andreas Saputra; Ben Jua Ivand Manihuruk (Politeknik Bisnis Indonesia, 2023)
In this digital era, medical record data in hospitals has grown to be very large and complex. This medical record data includes information about the patient, diagnosis, treatment, and other medical history. Efficient and effective management of medical record data is essential to improve the quality of health services, appropriate decision-making, and medical research. This study uses data mining techniques with the K-Means Clustering method to cluster patient medical record data. Cluster 1 consists of 1827 people suffering from Emergency, Orthopedics, Obgyn, Internal Medicine, Pulmonary, NICU/PISU, Heart Disease, Perinatology, Neonatal and Growth and Development, Obstetrics Oncology, as well as male and female 9227 and 8990 respectively. Cluster 4 consists of 417 people who suffer from Urology, ENT, General, Neurology, Rheumatology diseases, and the male gender is 195 people and the female gender is 112 people. by using data mining, researchers can find new information about how royal prima medan hospital manages various types of care. Researchers hope to be a reference for hospitals, to be able to socialize and prevent sources of disease based on gender and treatment.